Pemberdayaan Masyarakat Melalui Aktivitas Daur Ulang Sampah Berbasis Teks Prosedur di Media Sosial - Mochamad Syaefudin; Risna Nurtaci (UIN Siber Syekh Nurjati Cirebon, 2021)
Suranenggala Lor Village, Suranenggala District, Cirebon Regency has a fairly dense population with the majority of its citizens working as farmers. There are several problems in Suranenggala Lor Village, one of which is the accumulation of garbage on the side of Jalan Syekh Magelung Sakti. This is due to the lack of understanding of residents in processing and classifying waste. Therefore, it is necessary to take real action to the community by providing empowerment programs that are in accordance with their needs. However, because of the PPKM due to Covid-19, community empowerment activities in the form of waste recycling activities using a procedure text are carried out online on the social media page. This study uses a qualitative approach with the aim of research to determine the implementation of community empowerment programs. The results of the study indicate that there is an increase in the knowledge and ability of the community regarding processing and classifying waste so that these problems can be resolved.